Development and Quality Assessment of Fiber Enriched Nuggets of Kadaknath Chicken - Uikey, Shubham; Nayak, Narendra (Journal of Meat Science, 2019)
The present investigation was carried out with the prime objective of increasing fiber content by incorporating gram hulls. Upon con ducting various trials, on the basis of sensory attributes three best levels were selected. Efficacy of gram hulls at three different selected  levels (T1-4%, T2-6% & T3-8%) was assessed to increase the fiber content in kadaknath chicken nuggets. The pH value for control was  significantly (P
Keywords: Kadaknath nuggets; Gram hulls; Fiber enriched; Functional food